Effect of 15% carbohydrate mouth rinse on 10km running time trial - Leong, Kelvin Chua Kok (2018)
Background: Carbohydrate mouth rinsing has been shown to improve exercise performance in endurance events which deplete glycogen stores, and are no longer than 90 minutes. This is attributed to the carbohydrate sensing in the mouth which activates oral receptors that increases neural activity in regions of the brain which are associated with reward, thus improving motor drive or motivation (Carter, Jeukendrup, & Jones, 2004). However, there is a lack of studies investigating running time trials, as well as the use of 15% carbohydrate mouth rinse. Purpose: To investigate if a 15% carbohydrate mouth rinse has any effect on 10km running time trial. Performance measures are time taken to completion, participants’ heart rate (HR) and rate of perceived exertion (RPE). Method: A double-blinded, placebo controlled and randomized cross-over design was used for this study. Nine young, recreationally active, and healthy male participants performed two 10km running time trials with a carbohydrate (CHO) mouth rinse intervention and a placebo (PLA) mouth rinse control, following a familiarization session. Results: Significant increase in final mean time to completion for CHO trial as compared to PLA trial (p = 0.043; r = 0.334, decrease of 4.23min from 65.91min [55.64, 76.18] to 61.68min [52.44, 70.91]). No significant difference between HR (p = 0.260) and RPE (p > 0.99). Conclusion: 15% carbohydrate mouth rinse may not improve performance for 10km running time trial. Key words: carbohydrate mouth rinse, mouth rinse, carbohydrate, exercise performance